Risk of construction corruption factors in construction project life cycle from contractors’ perspectives - Mohd Saim, Nur Amylia Izrin (2021)
Oftentimes, construction industry is well known to be one the most easily corruptible industry in this world. This is due to the nature of the complexities of the industry itself, as there exists many loopholes that makes it easy for dishonest people looking to take advantage to gain for themselves. The practice of corruption in Malaysia have been severe as seen in the Corruption Perception Index (CPI) which ranked the country, 58th out of 180 countries in 2019. This makes it important to study the corrupt practices construction industry moreover it contributed to more than RM60 billion towards the Malaysian GDP. Corrupt practices not only affect the economic side of the nation but it also affects the government’s image as well as the nation’s reputation. Hence this study intended to identify the factors contributing to corruption throughout the construction project life cycle phases as it reveals the riskiest phases which are prone to corrupt practices. From literature review, it was found that there were around 200 corruption factors relating to the corruption in construction industry. After similarity checking, it was found that only 31 corruption factors were relevant which would then be placed under the construction project life cycle (CPLC) phases to categorize it. The pilot study involved 13 construction experts and the study found that all the construction corruption factor (CCF) to be relevant and the questionnaire reliable which is all Cronbach Alpha value above 0.600. The actual questionnaire survey was conducted among contractors from Grade 1 to 7 of the southern region of peninsular Malaysia. From 150 questionnaires distributed, the study managed to get back 135 sets which means 90% response rate. Data was then established from these 135 valid sets of questionnaires and was analysed using statistical tools and risk matrix chart. It was found that the collected data were reliable as the Cronbach alpha values shows it to be reliable. The data was further used to analyse the ranking of occurrence and severity for each factor in construction project life cycle (CPLC) phases. Based on the occurrence and severity values, the risk level of each factor was identified and plotted using risk matrix chart to show the riskiest factor in the CPLC. Finally, for the high risk factors, this study has proposed mitigation plan that will help to counter the corrupt practices. The findings from this study will assist the construction community in Malaysia to take appropriate actions in resolving the corruption issues with the suggested mitigation strategies for their organisations. For the relevant authorities, these findings can help to formulate rules and regulations to prevent corrupt practices and ensuring the construction activities can be carried out with a clean, high quality and in sustainable manner.